Accounting Gamified (Accmified) Sebagai Media Pembelajaran Interaktif Materi Siklus Akuntansi Perusahaan Jasa - Andriani, Jane; Hakim, Luqman; Listiadi, Agung (Universitas Hamzanwadi, 2023)
In this era of progress, learning innovation follows technological developments and student characteristics. The objectives of carrying out this research are: 1) to produce and test the feasibility of developing interactive media products for the basics of gamification-based institutional financial accounting, and 2) to analyze student responses to the use of interactive learning media for the basics of gamification-based institutional financial accounting. Research and Development was chosen as the research method with the ADDIE model. The research sample used was 35 class X students. The data obtained in this research was through interviews, observations, study sheets, validation sheets and questionnaires. The suitability of the media is tested using material, media, language expert validation instruments, as well as trials on students to determine responses and interest after using the media. The research results show that the interactive learning media development product in the form of this application obtained a material validation percentage of 84.17%, media validation of 100%, and language validation of 96.92%. The student response results reached 88.74%, so this application was declared very feasible and good for use in the learning process